Relationships between lower extremity power and fastball spin rate and ball velocity in professional baseball pitchers - Wong, R.; Laudner, K.; Amonette, W.; Vazquez, J.; Evans, D.; Meister, K. (The Journal of Strength and Conditioning Research, 2023)
Lower extremity power has been hypothesized to increase ball spin and velocity during pitching in baseball. Therefore, the purpose of this study was to determine the relationship between lower extremity power and fastball spin rate in professional baseball pitchers. A secondary purpose was to determine the relationship between lower extremity power and ball velocity. Fifty-three asymptomatic professional pitchers participated (24.5 ± 3.6 years; 189.9 ± 6.1 cm; 92.6 ± 10.3 kg). Each athlete performed 3 separate bilateral jump tests on force plates: countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ). The average fastball spin rate and ball velocity for each pitcher was calculated using a 3-dimensional Doppler radar and video system over the course of a competitive season. Standard multiple regression analyses (p = 0.05) revealed significant relationship between ball spin and summation of variables for the CMJ (peak force, peak power, rate of power development, and jump height) (R2 = 0.20, F = 3.1, p = 0.03). However, no individual variable was significantly associated (p > 0.09). There was also a significant amount of variance in ball spin explained by summation of variables for the SJ (peak force, peak power, rate of power development, and jump height) (R2 = 0.19, F = 2.8, p = 0.04); rate of power development was the only variable that significantly predicted ball spin within this model (B = 0.27; 95% confidence interval [CI]: 0.003-0.75, p = 0.05). Ball spin was not associated with summation of DJ variables (peak power, rate of power development, jump height, reactive strength index, and total peak power in watts) (R2 = 0.18, F = 2.0, p = 0.09). For ball velocity, there were no significant relationships for the summation of either the CMJ variables (R2 = 0.10, p = 0.28) or the SJ variables (R2 = 0.07, p = 0.44). However, there was a significant amount of variance in ball velocity explained by summation of variables for the DJ (R2 = 0.30, F = 3.93, p = 0.005). The reactive strength index was the sole unique contribution to this model (B = 1.18; 95% CI: -10.34 to 2.36, p = 0.002). These findings highlight the relevance of increased lower extremity power on increasing fastball spin rate and ball velocity.